Accuracy of Dermatoscopy in the Diagnosis of Basal Cell Carcinoma on the Skin of Head and Neck (AMJ (Advanced Medical Journal), 2023)
Background and objectives: Basal cell carcinoma is the commonest malignancy among all malignancies of the body. Sun exposure plays an important role in its pathogenesis. Basal cell carcinoma usually is localized and metastasizes rarely. Dermatoscopy is a new non-invasive surface microscopic examination of the skin. It is proven to play a significant role in the early diagnosis of BCC. The aim of the study is to evaluate the dermatoscopic features of basal cell carcinoma lesions.Methods: One hundred and seventy lesions on the head and neck of patients were suspected of BCC dermatoscopically and included in the study. Biopsies of the lesions were sent 140 for histopathological confirmation. Dermatoscopic pictures of each lesion are saved as pictures through a camera adapted to the dermatoscopy. Data and dermatoscopic pictures were evaluated and analyzed statistically.Results: Diagnosis of basal cell carcinoma was confirmed for 163 lesions out of 134 patients with head and neck BCC lesions. The majority of patients had photo type III (75.3%). The most common clinical type was ulcerative (74 lesions, 45.4%). Pigmented lesions were 107 (65.6%) basal cell carcinoma lesions. The sensitivity of dermatoscopic diagnosis of BCC was 95.8%. Eight dermatoscopic features were observed in the lesions. The most common dermatoscopic finding was vascular (126, 77, 3%) and the most common vascular feature was arborizing blood vessels. Conclusions: Dermatoscopy is a useful noninvasive visual aid in the diagnosis of basal cell carcinoma and its sensitivity is usually above 95%. Histopathology of basal cell carcinoma may remain in the future as a tool for control of its treatment only.